Berthier's Journal de Trévoux and the philsophes - Pappas, J (Voltaire Foundation, 2017)
Foreword Part One I. The Journal de Trévoux II. Guillaume François Berthier Part Two I. Montesquieu II. Voltaire III. Rousseau IV. Diderot and the Encyclopédie V. The Journal de Trévoux and the Enlightenment Conclusion List of sources Index